Liposomal bupivacaine versus conventional anesthetics in adductor canal block for total knee arthroplasty: a meta-analysis of randomized controlled trials - Xiaoli Ye; Kaixi Shang; Lina Zhao; Quan Liang; Huanzhen Luo; Jing Shi (BMC Anesthesiology)
Abstract Background: Total Knee Arthroplasty (TKA) requires effective perioperative pain management. The Adductor Canal Block (ACB) is widely used, traditionally administered with conventional anesthetics (e.g., ropivacaine or bupivacaine) that provide limited analgesic duration. Liposomal bupivacaine (LB), with its sustained-release properties, is a promising alternative; however, its efficacy in ACB for TKA remains debated. This meta-analysis aimed to compare LB with conventional anesthetics in ACB for TKA. Methods: Following PRISMA guidelines, we systematically searched PubMed, EMBASE, Cochrane Library, and Web of Science up to December 15, 2024, for randomized controlled trials (RCTs) evaluating adult patients undergoing TKA who received ACB with either LB or conventional anesthetics. A total of 4 high-quality RCTs (involving 343 patients) were included. Primary outcomes were postoperative pain scores [assessed via Visual Analog Scale (VAS) / Numerical Rating Scale (NRS)], opioid consumption, length of hospital stay (LOS), and adverse events. The quality of included RCTs was evaluated using the revised Cochrane Risk of Bias 2 (RoB2) tool, and meta-analysis was performed with RevMan 5.4.1 software. Results: Compared with conventional anesthetics, LB resulted in statistically significant reductions in pain scores at postoperative day (POD) 0 (VAS/NRS decrease: 1.77 units; weighted mean difference [WMD] = -1.77; 95% CI: -2.41 to -1.13; P < 0.001) and POD 1 (0.81 units; WMD = -0.81; 95% CI: -1.30 to -0.32; P = 0.001), as well as opioid consumption at POD 0 (4.19 mg; WMD = -4.19; 95% CI: -6.76 to -1.63; P = 0.001) and POD 1 (8.22 mg; WMD = -8.22; 95% CI: -10.65 to -5.80; P < 0.001). These benefits were restricted to the short-term (POD 0–1); no significant differences were observed in pain scores, opioid use, LOS (WMD = 1.02; 95% CI: -0.46 to 2.50; P = 0.18), or adverse events (odds ratio [OR] = 0.73; 95% CI: 0.33 to 1.58; P = 0.42) beyond POD 1. Conclusions: LB in ACB for TKA provides statistically significant short-term (POD 0–1) pain relief and reduces opioid consumption compared with conventional anesthetics, with comparable LOS and adverse events. However, these findings should be interpreted cautiously due to the limited sample size (4 RCTs, 343 patients). Larger, well-designed RCTs are required to confirm its long-term clinical efficacy.